2019
DOI: 10.1071/en18235
|View full text |Cite
|
Sign up to set email alerts
|

Molecular fractionation of dissolved organic matter on ferrihydrite: effects of dissolved cations

Abstract: Environmental contextCarbon sequestration and dynamics are influenced by adsorptive fractionation of dissolved organic matter (DOM) on minerals. We found that the molecular fractionation of DOM on ferrihydrite was highly dependent on the presence of Na, Ca and Cu ions in water. These results advance our mechanistic understanding of the dynamic behaviour of DOM, and contribute to predicting carbon cycling and contaminant behaviour in the natural environment. AbstractThe adsorptive fractionation of dissolved org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 52 publications
3
28
1
Order By: Relevance
“…To minimize the adjustable parameters in model calculations, we did not alter the Δ LK 2 value either, which usually accounted for the strong binding sites due to the nitrogen- or sulfur-containing groups. Our previous study also indicated that the adsorptive fractionation of DOM molecules on iron oxyhydroxides changed the concentrations of carboxylic groups in DOM . Therefore, during the model calculations for FA supernatant samples after adsorptive fractionation, only the site density of carboxylic groups (i.e., n A , mmol (g FA) −1 ) was adjusted in WHAM 7, and log K MA and Δ LK 2 were kept unchanged (i.e., log K MA = 1.95 and Δ LK 2 = 1.75).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize the adjustable parameters in model calculations, we did not alter the Δ LK 2 value either, which usually accounted for the strong binding sites due to the nitrogen- or sulfur-containing groups. Our previous study also indicated that the adsorptive fractionation of DOM molecules on iron oxyhydroxides changed the concentrations of carboxylic groups in DOM . Therefore, during the model calculations for FA supernatant samples after adsorptive fractionation, only the site density of carboxylic groups (i.e., n A , mmol (g FA) −1 ) was adjusted in WHAM 7, and log K MA and Δ LK 2 were kept unchanged (i.e., log K MA = 1.95 and Δ LK 2 = 1.75).…”
Section: Methodsmentioning
confidence: 99%
“…The adsorptive fractionation of DOM on ferrihydrite and the effects of dissolved cations (e.g., Cu 2+ , Ca 2+ , Na + ) on DOM fractionation have been illustrated at the molecular level, but the effects of anions such as phosphate on DOM fractionation still limit our knowledge about the interactions between the mineral and the organic matter in natural environments. Phosphate is a common oxyanion and exhibits a high affinity to iron oxide surfaces (e.g., ferrihydrite) .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the application of coal fly-ash on peat resulted in an increase in the concentration of soluble Fe (Figure 2C) and the content of exchangeable Ca (Figure 2D). Multivalent cations such as Ca 2+ and Fe 3+ are able to bind the functional groups of organic matter (COO − ) through the adsorption process so that the organic matter cannot be decomposed by soil microorganisms, and thereby decreasing the amounts of carbon mineralization products (CO2 and CH4) [14,25,26].…”
Section: Influence Of Coal Fly-ash Application On Production Of Co2 and Ch4mentioning
confidence: 99%
“…Higher water alkalinity and HCO 3 − at inlets resulted from the anaerobic decomposition of particulate organic matter, and then [H + ] increased accordingly, which made pH values at inlets lower than in the central lake region. Higher molecular weight and aromaticity of DOM was preferentially fractionated onto iron minerals, and cations (Ca, Na and Cu) intercalated between organic matter and iron by bridging to form organic mineral complexes [31,32]. When oxygen is rapidly depleted, microorganisms use oxidized components such as NO 3 − , Mn(IV), Fe(III) and SO 4 2− as electron acceptors for the decomposition of organic matter [33].…”
Section: Surface and Underlying Watermentioning
confidence: 99%
“…It was reported that microbially mediated reduction reactions of Fe(OH) 3 , SO 4 2− and NO 3 − consumed protons when organic matter oxidized and were responsible for the increase of pH [33]. Thus, reduced Fe(II), together with certain ratios of Ca/Mg, were unbound from clay carbonate [31,32]. Co, Sc and Sr were observed to decrease obviously with depth, which was quite the opposite of the ratio of Ca/Mg (R 2 = 0.7, p ≤ 0.01), having been explained as the same mechanisms to pore water at DC-2 that reverse complexation/encapsulation or cations exchange happened [48,49].…”
Section: Pore Water At Dc-2 and Dc-9mentioning
confidence: 99%